Physical and mental health in HIV-infected patients with virological success and long-term exposure to antiretroviral therapy. Issue 4 (3rd April 2021) - Sabranski, Michael; Erdbeer, Gesa; Sonntag, Ina; Stoehr, Albrecht; Horst, Heinz-August; Plettenberg, Andreas; Lebherz, Lisa; Stellbrink, Hans-Jürgen; Hoffmann, Christian
ABSTRACT: In people living with HIV (PLWH), a decade-long antiretroviral therapy (ART) poses new challenges regarding physical and mental health. The aim of this cross-sectional study is to investigate the health-related quality of life (HRQOL) in adult HIV-infected patients with viral suppression and an ART exposure for at least 5 years in three German HIV centers. Patients were evaluated by the ACTG Augmented Symptoms Distress Module (ASDM) and the SF-12 Health Survey. Among 894 patients, symptom-related distress was highly prevalent. The most common symptoms were fatigue, insomnia, sadness and depression, sexual dysfunction, and changes in body appearance. In the multivariate analysis, ART duration, age and depression were significantly associated with a higher overall symptom summary score. Self-reported mean SF-12 scores were lower for mental health and younger patients compared to the standard random sample of a healthy German population. Depression and occupational status were significantly related to a lower physical component summary score, by contrast older age was associated with higher scores in the mental component summary, implying more favorable mental health status. In this large group of PLWH, the degree of symptom-related distress was high. Mental and physical health should be considered an integral part of ongoing HIV care.